Anti-PD-1 Therapy is Beneficial for the Survival of Patients with Oral Squamous Cell Carcinoma - Feng L; Yin K; Zhang S; Chen Z; Bao Y; Li T (Cancer Management and Research, 2022)
Liang Feng,1 Ke Yin,2 Suxin Zhang,3 Zhong Chen,3 Yang Bao,3 Tianke Li3 1Department of Stomatology, Baoding First Central Hospital, Baoding, Hebei, People’s Republic of China; 2Department of Stomatology, Xingtai People’s Hospital, Xingtai, Hebei, People’s Republic of China; 3Department of Stomatology, The Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Tianke Li, Department of Stomatology, The Fourth Hospital of Hebei Medical University, No. 12 Jiankang Road, Shijiazhuang, Hebei, 050000, People’s Republic of China, Email litianb112@163.comBackground: Oral squamous cell carcinoma (OSCC) is one of the most common malignant tumors of the head and neck. Programmed cell death protein 1 (PD-1), and programmed cell death 1 ligand 1 (PD-L1) are often overexpressed in OSCC patients, and their expression level is closely related to tumor prognosis. The objectives of this study were: 1) to evaluate the impact of anti-PD-1 treatment on the immune system and prognosis of OSCC patients and 2) to find possible associations between T-cell immunity and anti-PD-1 therapy.Methods: A total of 120 patients (divided into two equal groups: “non-anti-PD1 therapy” and “anti-PD1 therapy”) with pathologically diagnosed OSCC participated in the study. Fresh peripheral blood samples (1 mL) were collected 2 days before and 20 days after the treatment. Heparin was used as an anticoagulant. Kaplan–Meier curves were plotted to compare the non-anti-PD-1 therapy and anti-PD-1 therapy groups.Results: Based on the Spearman-rho test, we found a significant correlation between anti-PD-1 treatment and survival time (P< 0.001). Univariate/multivariate Cox regression analysis revealed that anti-PD-1 therapy is a significant independent risk factor of 5-year overall survival (OS) in OSCC patients (HR: 0.110, 95% CI: 0.062– 0.195, P< 0.001). One-way ANOVA showed that the mean levels of IFN-γ and IL-2 and numbers of CD4+ T cells were significantly increased in the anti-PD-1 therapy group compared with the non-anti PD-1 therapy group (control). The was no change in the number of CD8+ cells between the two groups. Kaplan–Meier curve results showed that the OS of patients in the anti-PD-1 therapy group was significantly longer than that in the non-anti-PD-1 therapy group.Conclusion: Anti-PD-1 therapy is beneficial to the survival and prognosis of patients with OSCC, improves T-cell immunity, and enhances tumor regression.Keywords: OSCC, oral cancer, PD-1, PD-L1, targeted therapy, Squamous cell carcinoma